2000
DOI: 10.1046/j.1365-246x.2000.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

On galvanic distortion of regional 3-D MT impedances On galvanic distortion of regional three-dimensional magnetotelluric impedances

Abstract: S U M M A RYIn magnetotelluric (MT) studies, the observed response function (the MT impedance) usually su¡ers from galvanic distortions due to near-surface inhomogeneities. Removal of these e¡ects is essential to obtain an accurate model of the subsurface electrical conductivity structure. Galvanic distortion is usually expressed by a simple real tensor multiplying the undistorted regional impedance. The problem still remains of how to solve the ensuing linear equations in order to determine the distortion ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…Here, the period range was selected to sense a structure existing between 10 and 100 km in depth. Therefore, any small structures confined in the near-surface layer of a few kilometers or less, which is shallower than the inductive scale length of present interest, are considered to be galvanic distorters (Utada and Munekane 2000). We further assume for simplicity that galvanic distorters have…”
Section: Estimation Of a Model Of The Regional Mean 1d Profilementioning
confidence: 99%
See 3 more Smart Citations
“…Here, the period range was selected to sense a structure existing between 10 and 100 km in depth. Therefore, any small structures confined in the near-surface layer of a few kilometers or less, which is shallower than the inductive scale length of present interest, are considered to be galvanic distorters (Utada and Munekane 2000). We further assume for simplicity that galvanic distorters have…”
Section: Estimation Of a Model Of The Regional Mean 1d Profilementioning
confidence: 99%
“…In addition, the static shift could be corrected with the TEM data with some limitations (see Watts et al 2013;Tournerie et al 2007;Wilt and Williams 1989), e.g., when the heterogeneity is smaller than the transmitter loop. Utada and Munekane (2000) attempted to solve this problem by introducing Faraday's law as a constraint, but the solution was not practical. The numerical examples presented here show that the concept of the apparent gain can be used to approximate the site gain in the assumed situation.…”
Section: Apparent Gainsmentioning
confidence: 99%
See 2 more Smart Citations
“…For 2-D data, application of the techniques proposed by Zhang et al (1987), Jones (1988), Bailey (1989, 1991), Bahr (1991), Groom and Bahr (1992), Jones and Groom (1993), Chakidri et al (1992), Chave and Smith (1994), Smith (1995), Spitzer (2001), and Ledo et al (2002b) usually suffice. For 3-D data, the methods proposed by Ledo et al (1998), Utada et al (2000), and Garcı´a and Jones (2002) are advocated. A complete review of different aspects and techniques can be found in the reviews by Jones (1983), Jiracek (1990) and Ogawa (2002).…”
Section: Data Selectionmentioning
confidence: 99%